Acquisition of Demonstratives in English and Spanish - González-Peña, Patricia; Doherty, Martin J.; Guijarro-Fuentes, Pedro (Frontiers in Psychology, 2020)
The present work re-evaluates the long-standing claim that demonstratives are among infants earliest and most common words, principally based on single case diaries (E. Clark, 1978). Although demonstratives are deictic words important for joint attention, deictic gestures and non-word vocalisations could serve this function in early language development; thus the role of demonstratives may have been overestimated. We use extensive data from the CHILDES corpora (Study 1, N = 65, 265 transcripts) and McArthur-Bates CDI database (Study 2, N = 950). The language production of 18- to 24-month-old Spanish and English learners was analysed to determine the age and order of acquisition, and frequency of demonstratives. Results indicate that demonstratives do not typically appear before the 50th word and are more frequent from the two-word utterance stage than early in language development. Corpus data show few differences between Spanish and English, whereas parental report data suggest much later acquisition for demonstratives in English. These findings expand our knowledge of the development of deictic communication, and of the methodological challenges of assessing early production of function words.